The properties of gases and liquids - Poling, Bruce E. (McGraw-Hill, 2001)
The estimation of physical properties - Pure component constants - Thermodynamic properties of ideal gases - Pressure-volume-temperature relationships of pure gases and liquids - Pressure-volume.temperature relatonships of mixtures - Thermodynamic properties of pure components and mixtures - Vapor pressures and enthelpies of vaporization of pure fluids - Fluid phase equilibria in multicomponent systems - Viscosity - Thermal conductivity - Diffusion coefficients - Surface tension - Appendices.